2020
DOI: 10.1002/joc.6701
|View full text |Cite
|
Sign up to set email alerts
|

Climatology and trend analysis (1987–2016) of fire weather in the Euro‐Mediterranean

Abstract: High-resolution regional climate simulations were conducted for the past 30 years (1987-2016), focusing on the Euro-Mediterranean region. The numerical simulations were used for computing the Canadian Fire Weather Index, for deriving the climatology of fire weather in the study area and investigating the presence of long-term trends, with particular emphasis on extremes during the May to September period. Results suggest that the Euro-Mediterranean fire weather follows a zonal pattern, characterized by adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Moreover Bedia et al (2014); Amatulli et al (2013) estimated the future fire danger using the FWI for several countries bordering the Mediterranean and found out that there is a strong correlation of the index with burnt area for the Mediterenean region, whereas that correlation is weaker when individual countries were examined. Giannaros et al (2021) used the number of days with FWI > 30 as an index for the assessment of fire weather extremes in the Euro-Mediterranean. Focusing on Greece Karali et al (2014) have correlated the number of fires with the FWI in order to determine the fire-related, region-specific thresholds for the FWI.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover Bedia et al (2014); Amatulli et al (2013) estimated the future fire danger using the FWI for several countries bordering the Mediterranean and found out that there is a strong correlation of the index with burnt area for the Mediterenean region, whereas that correlation is weaker when individual countries were examined. Giannaros et al (2021) used the number of days with FWI > 30 as an index for the assessment of fire weather extremes in the Euro-Mediterranean. Focusing on Greece Karali et al (2014) have correlated the number of fires with the FWI in order to determine the fire-related, region-specific thresholds for the FWI.…”
Section: Introductionmentioning
confidence: 99%
“…Natural hazards drive major damages to communities, infrastructure, and ecosystems across the globe. Recent European floods (Cornwall, 2021), droughts in South Africa (Pascale et al., 2020), and wildfires (for example in the United States (Swain, 2021) and Euro‐Mediterranean region (Giannaros et al., 2021)) highlight how human and natural systems are exposed and vulnerable to natural hazards. Between 2000 and 2019, natural hazard‐related disasters caused over one million deaths worldwide and over two trillion U.S. dollars in global economic losses (United Nations Office for Disaster Risk Reduction, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the spatiotemporal variability of fire weather conditions over the last decades in the Euro-Mediterranean area has attracted many researchers' interest (among others, [8][9][10][11]). For example, Giannaros et al [11] has recently provided a spatiotemporal mapping of fire weather conditions in Europe and the Mediterranean, aiming to investigate potential long-term trends of fire weather conditions (period 1987-2016). The authors reported an increasing occurrence of extreme fire weather conditions over the Iberian Peninsula and eastern Balkans, and decreasing trends over the southeast Mediterranean.…”
Section: Introductionmentioning
confidence: 99%
“…Using data for the last decade, namely number of wildfires (including burnt areas) provided by the Fire Services of the participating countries and daily values of CFWI calculated from available meteorological data (mainly model derived re-analyses, detailed also in [11]), the CFWI thresholds for fire danger that are more appropriate to the fire environment of the three countries are being revisited. For the case of Bulgaria, a complex approach to fire danger assessment based on the use of fire weather indices considering the fuel dryness and the soil moisture deficit has also been explored.…”
mentioning
confidence: 99%